Impact of Opioid Prescribing Guidelines on Postoperative Opioid Prescriptions Following Elective Spine Surgery: Results From an Institutional Quality Improvement Initiative. Issue 3 (September 2021) - Krauss, William E; Habermann, Elizabeth B; Goyal, Anshit; Ubl, Daniel S; Alvi, Mohammed Ali; Whipple, Daniel C; Glasgow, Amy E; Gazelka, Halena M; Bydon, Mohamad
Abstract : BACKGROUND : With a dramatic rise in prescription opioid use, it is imperative to review postsurgical prescribing patterns given their contributions to the opioid epidemic. OBJECTIVE : To evaluate the impact of departmental postoperative prescribing guidelines on opioid prescriptions following elective spine surgery. METHODS : Patients undergoing elective cervical or lumbar spine surgery between 2017 and 2018 were identified. Procedure‐specific opioid prescribing guidelines to limit postoperative prescribing following neurosurgical procedures were developed in 2017 and implemented in January 2018. Preguideline data were available from July to December 2017, and postguideline data from July to December 2018. Discharge prescriptions in morphine milliequivalents (MMEs), the proportion of patients (i) discharged with an opioid prescription, (ii) needing refills within 30 d, (iii) with guideline compliant prescriptions were compared in the 2 groups. Multivariable (MV) analyses were performed to assess the impact of guideline implementation on refill prescriptions within 30 d. RESULTS : A total of 1193 patients were identified (cervical: 308; lumbar: 885) with 569 (47.7%) patients from the preguideline period. Following guideline implementation, fewer patients were discharged with a postoperative opioid prescription (92.5% vs 81.7%, P < .001) and median postoperative opioid prescription decreased significantly (300 MMEs vs 225 MMEs, P < .001). The 30‐d refill prescription rate was not significantly different between preguideline and postguideline cohorts (pre: 24.4% vs post: 20.2%, P = .079). MV analyses did not demonstrate any impact of guideline implementation on need for 30‐d refill prescriptions for both cervical (odds ratio [OR] = 0.68, confidence interval [CI] = 0.37‐1.26, P = .22) and lumbar cohorts (OR = 0.95, CI = 0.66‐1.36, P = .78). CONCLUSION : Provider‐aimed interventions such as implementation of procedure‐specific prescribing guidelines can significantly reduce postoperative opioid prescriptions following spine surgery without increasing the need for refill prescriptions for pain control.